Balance hídrico superficial de la cuenca del río Sisa - Vásquez Fernández, Claudio (2001)
This work, which has been accepted by the Faculty of Civil Engineering of the National University of San Martín as thesis, whose area of action is located in the Region San Martín. Has been developed taking into account as a bibliographic reference the methodological guide for the surface water Balance of Latin America; Indeed the Balance water surface of the basin of the river Sisa is calculated depending on the history existing, bone of them controls rainfall e hydrometric. •For therefore have been considered parameters (P) precipitation, evapotranspiration Real (ETR) and surface runoff (R); the average annual values represent each parameter. Precipitation (P) Although, theoretically it is not difficult to measure promptly, but problems of contouring and installation the water captured by the instruments may be different that actually falls and considering that inside the. basin, the network pluviometric e...